Geostatistical and space geodetic methods applied to 3D coseismic displacement field : mapping earthquakes from space - Stein, A. (University of Twente Faculty of Geo-Information and Earth Observation (ITC), 2020)
PhD thesis Univesity of Twente, Summary in English